Analysis of the interaction between the macroalgae Rugulopteryx okamurae (Ochrophyta) and the hydrological properties of the Alboran Sea over the past years. - Nadal Arizo, Irene; García-Lafuente, Jesús; Sammartino, Simone; Sánchez-Garrido, José Carlos; Korbee-Peinado, Nathalie; López-Figueroa, Félix (My University, 2024)
Since its first detection in the Strait of Gibraltar in 2015 (Altamirano, 2016), the exotic brown-algae Rugulopteryx okamurae has massively expanded through the westernmost coasts of the Mediterranean Sea. This species occupies shallow rocky bottoms with coverages ranging from 80-100%, producing serious impacts over the benthic communities previously established, and causing accumulations of thousands of tons in the coastal shores of the Strait of Gibraltar, Alboran Sea and Gulf of Cadiz, affecting fisheries and tourism. Currently, there is no consensus about the reasons explaining its invasive capacity and rapid dispersal, although favorable environmental conditions in the Mediterranean Sea have been recently suggested as the key factor (Muñoz et al., 2019). To gain insight into the invasion and settlement of Rugulopteryx okamurae, time-series of nutrients, temperature, and salinity were analyzed in the Strait recently by Mercado et al. (2022). The present work extends the analysis of these authors to investigate the long-term variability and anomalies of environmental variables (SST, salinity, current velocities, organic and inorganic nutrients, phytoplankton abundance, chlorophyll, and solar radiation) in the Strait of Gibraltar, Alboran Sea, and Gulf of Cadiz. Some preliminary results are presented.
Keywords: Algas marinas - Dispersión; Oceanografía; Rugulopteryx okamurae; Strait of Gibraltar; Invasive species